Ägyptische Rituale der griechisch-römischen Zeit - Quack, Joachim Friedrich (Orientalische Religionen in der Antike, 2014)
There is an abundance of preserved Egyptian rituals which are characterized as much by their variety (temple cult, private use for the living and the dead) as they are by the wide range of levels of language development and writing systems which originated in Egypt during the Greco-Roman Period(approximately 330 BC to 200 AD). The articles in this volume deal with various aspects of this subject and are enhanced by a study of simultaneous phenomena in Mesopotamia
Beitr. teilw. dt., teilw. engl., teilw. franz. - Literaturangaben
Keywords: Egypt -- Religion -- 332 B.C.-640 A.D -- Congresses; Egypt -- Civilization -- 332 B.C.-638 A.D -- Congresses; Konferenzschrift -- 2008 -- Heidelberg; Aufsatzsammlung; Geschichte 332 v. Chr.-395; Ritus; Ägypten